2020
DOI: 10.3892/ijo.2020.5097
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone inhibits stemness maintenance and enhances chemosensitivity of hepatocellular carcinoma stem cells by inducing deSUMOylation of HIF‑1α and Oct4

Abstract: It has been controversial whether patients with hepatocellular carcinoma (HCC) should receive glucocorticoid therapy during chemotherapy. Recent studies have demonstrated that glucocorticoids increase the therapeutic sensitivity of tumors to some chemotherapeutic drugs, but the specific mechanism remains unclear. In the present study, dexamethasone (Dex) was used to treat HCC stem cells. The results demonstrated that Dex reduced stemness maintenance and self-renewal of HCC stem cells, promoted epithelial-to-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…On the contrary, several studies have shown that dexamethasone decreases Sox2 and thereby inhibits cancer stem cells. 24 , 25 In addition, similar to our study, dexamethasone did not promote Ror1 expression in pancreatic cells 24 (Figure 2C ). Together these results indicate that GCs are a regulator of Sox2 expression, however, its activation or inhibition is dependent upon the cell type and/or microenvironment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, several studies have shown that dexamethasone decreases Sox2 and thereby inhibits cancer stem cells. 24 , 25 In addition, similar to our study, dexamethasone did not promote Ror1 expression in pancreatic cells 24 (Figure 2C ). Together these results indicate that GCs are a regulator of Sox2 expression, however, its activation or inhibition is dependent upon the cell type and/or microenvironment.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that dexamethasone promoted expression of the pluripotency transcription factor Sox2 in both normal diet and obese mice (Figure 2B), potentially indicating that a longer treatment time may promote stemness in lean mice. On the contrary, several studies have shown that dexamethasone decreases Sox2 and thereby inhibits cancer stem cells 24,25 . In addition, similar to our study, dexamethasone did not promote Ror1 expression in pancreatic cells 24 (Figure 2C).…”
Section: Discussionsupporting
confidence: 87%
“…2B), potentially indicating that a longer treatment time may promote stemness in lean mice. On the contrary, several studies have shown that dexamethasone decreases Sox2 and thereby inhibits cancer stem cells [24,25]. In addition, similar to our study, dexamethasone did not promote Ror1 expression in pancreatic cells [24] (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In HCC, several factors have been identified that are highly relevant to stemness, including p53 mutation, β-catenin mutation, and telomerase reverse transcriptase promoter mutation ( 28 ). Recently, it is also proposed that SUMOylation plays a key role in HCC stemness ( 29 ), which highlights the possibility of SENP2 as a regulator for HCC stemness. Meanwhile, as mentioned earlier, our study disclosed that SENP2 was decreased in CSCs of HCC cells.…”
Section: Discussionmentioning
confidence: 99%